Genetic background influences pig growth rate responses to porcine circovirus type 2 (pcv2) vaccines - Potter, M. L.; Tokach, Lisa M.; Henry, Steven C.; DeRouchey, Joel M.; Tokach, Michael D.; Rowland, Raymond R. R.; Oberst, Richard D.; Hesse, Richard A.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 454 pigs (21 d of age, 13.4 lb) were used in a 130-d field study to investigate porcine circovirus type 2 (PCV2) vaccine effects on growth performance of boars and gilts of 4 different genetic backgrounds: A×A (Duroc-based sire and dam), B×B (synthetic line sire and dam lines derived from Duroc, Pie-train, and Large White), A×B, and B×A. Pigs were identified as potential test pigs at birth and ear tagged for identification. Characteristics including litter, genetic background, gender, and birth weight were recorded and used in allotting PCV2 vaccine treatment groups. Pigs were vaccinated according to label dose with a 2-dose commercial PCV2 vaccine (Circumvent PCV, Intervet Inc., Millsboro, DE) at weaning (d 0) and again 14 d later. Vaccinated and control pigs were comingled within the same pen for the duration of the study. Pigs were individually weighed on d 0, 40, and 130 to measure growth rate. Backfat and loin depth were measured on d 130 by using real-time ultra-sound. Blood was collected on d 0, 40, and 130 for indirect fluorescent antibody measurement of PCV2 antibodies and polymerase chain reaction (PCR) analysis for determination of PCV2 virus load. By d 130, vaccinates were heavier (P < 0.01) than controls. However, the magnitude of the weight difference between control and vaccinates was almost 4 times greater in the A×A pigs than in the B×B pigs (P < 0.05). On the basis of growth performance, the different genetic backgrounds responded differently to the PCV2 vaccination even though they were comingled in the same pen. In the 2 pure-line populations, even the best performing portion of the population appeared to benefit from vaccination, suggesting that growth performance of most pigs is being affected by PCV2 infection. Control pigs exhibited a late increase in PCV2 antibody levels, a consequence of natural infection. In contrast, vaccinated pigs did not exhibit a late-finisher antibody rise. Vaccinated pigs possessed a decreased viral load (as quantified by PCR PCV2 viral DNA) at both d 40 and 130. The data demonstrate that genetic background affects either the expression of porcine circoviral disease or the response to the PCV2 vaccine.
Keywords: Circovirus; Genetics; Growth; PCV2; Swine; Vaccination